Pelatihan Teknologi Digital dan Penghematan Energi Berbasis Panel Surya untuk Keluarga Mandiri pada Ibu-Ibu PKK di Dusun Brendil Ngawi - Yuniahastuti, Irna Tri; Yudha Adi Kusuma; Ridam Dwi Laksono (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The development of digital technology and the increasing need for energy are challenges as well as opportunities in community empowerment efforts, especially in rural areas. Providing targeted and applicable training on the use of digital technology and energy savings based on solar panels is a solution to overcome these problems. The training was conducted on 25 PKK mothers in the Brendil Ngawi hamlet. The results of this training showed an increase in knowledge about digital technology and an increase in knowledge about solar panels by more than 50% of the total participants. It is hoped that after this training, PKK mothers will be able to apply this knowledge in their respective household lives so that they can form independent and self-sufficient families.